Combination of Laser and Thermal Sintering of Thermoelectric Ca3Co4O9 Films. Issue 1 (10th November 2021) - Wolf, Mario; Rehder, Lena; Steinbach, Frank; Abt, Marvin; Hinterding, Richard; Overmeyer, Ludger; Feldhoff, Armin
Abstract: The manufacturing technology of thermoelectric materials is laborious and expensive often including complex and time‐intensive preparation steps. In this work, a laser sintering process of the oxide‐based thermoelectric material Ca3 Co4 O9 is investigated. Samples based on spray‐coated Ca3 Co4 O9 were prepared and subsequently sintered under various laser parameters and investigated in terms of the microstructure and thermoelectric properties. Here, the combination of laser sintering and subsequent thermal sintering proved to be a promising concept for the preparation of thermoelectric films. Laser sintering can thus make a great contribution in improving the processing of thermoelectric materials, especially when films are applied that cannot be sintered under pressure. Abstract : Laser sintering as promising alternative and addition sintering process in manufacturing of thermoelectric materials is investigated by laser treatment of a ceramic Ca3 Co4 O9 film. The microstructure and the thermoelectric properties are analyzed to evaluate the effect of the laser and compared to conventional thermal sintering methods.